1987
DOI: 10.1099/00222615-23-4-289
|View full text |Cite
|
Sign up to set email alerts
|

Structure and biology of Shigella flexneri O antigens

Abstract: The species Shigellajiexneri comprises a serologically heterogeneous group of dysentery bacilli whose 0 antigens are polysaccharide-lipid Apolypeptide-lipid B complexes strictly comparable in their gross structural and biological properties to the analogous antigens present in all gram-negative bacilli of the family Enterobacteriaceae (Simmons, 1971a). As shown in fig. 1, the lipopolysaccharide (LPS) component of these antigens comprises two distinct regions-a common basal structure shared by all S . JIexneri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
97
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(97 citation statements)
references
References 31 publications
0
97
0
Order By: Relevance
“…As in other smooth organisms, the LPS of Shigella spp. contains a lipid A region, a core oligosaccharide, and an O-antigen polysaccharide side chain whose composition varies among different serotypes of Shigella (Kenne et al, 1978;Simmons and Romanowska, 1987;Brahmbhatt et al, 1992) (LPS of Shigella flexneri 2a is shown in Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in other smooth organisms, the LPS of Shigella spp. contains a lipid A region, a core oligosaccharide, and an O-antigen polysaccharide side chain whose composition varies among different serotypes of Shigella (Kenne et al, 1978;Simmons and Romanowska, 1987;Brahmbhatt et al, 1992) (LPS of Shigella flexneri 2a is shown in Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%
“…1. Lipopolysaccharide (LPS) structure of S. flexneri serotype 2a and some of the genes involved in the LPS synthesis in S. flexneri (Kenne et al, 1978;Simmons and Romanowska, 1987). A. LPS structure and brief synthesis pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Except for S. sonnei, each species contains multiple serotypes based on the structure of the O antigen, and, at least 49 serotypes of Shigella have been recognized, representing subtypes from three of the four groups; of which 15 belong to S. flexneri (Simmons & Romanowska 1987, Bopp et al 2003.…”
mentioning
confidence: 99%
“…1). It has been shown that bacteriophage has the ability to cause such modification of the O-antigen by the addition of group-antigens 7, 8 and 6 (20,23). We have previously cloned and sequenced the gene encoding glucosyl transferase (gtr) from phage SIX (22).…”
mentioning
confidence: 99%